COMPARATIVE ANALYSIS OF THE FACTORS ATTRACTING FDI: THE EXPERIENCE OF CENTRAL ASIAN COUNTRIES (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article explores the key factors influencing Foreign Direct Investment (FDI) inflows into Central Asian countries—Kazakhstan, Uzbekistan, Turkmenistan, Kyrgyzstan, and Tajikistan. Despite their vast natural resources and strategic location, these countries face significant challenges in attracting foreign investment.